2021
DOI: 10.2147/jir.s308558
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Contributes to Uterine Quiescence Through Inhibition of NLRP3 Inflammasome Activation by Suppressing the TLR4/NF-κB Signalling Pathway

Abstract: Background The NLRP3 inflammasome plays a critical role in inflammatory responses in various diseases. Our previous study showed that NLRP3 expression was significantly increased in human pregnancy tissue during term labour. Therefore, we explored whether NLRP3 participated in inflammatory responses of preterm and term labour and whether this process could be relieved by H 2 S, one anti-inflammatory gasotransmitter. Methods Human myometrium was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Several in vitro studies have shown that during pregnancy the production of H 2 S by the uterine vascular smooth cells is increased and this facilitates uterine quiescence 23,24 . Other mouse studies of PTD induced by LPS have shown that H 2 S acts as a counter anti‐inflammatory mechanism which inhibits NLRP3‐inflammasome activation and the subsequent cleavage of pro‐IL‐1β to the active IL‐1β moiety 14,25 . In these studies the role of endogenous H 2 S production through gene knock‐outing has not been studied; retardation of PTD was achieved through the administration of the H 2 S donor sodium sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies have shown that during pregnancy the production of H 2 S by the uterine vascular smooth cells is increased and this facilitates uterine quiescence 23,24 . Other mouse studies of PTD induced by LPS have shown that H 2 S acts as a counter anti‐inflammatory mechanism which inhibits NLRP3‐inflammasome activation and the subsequent cleavage of pro‐IL‐1β to the active IL‐1β moiety 14,25 . In these studies the role of endogenous H 2 S production through gene knock‐outing has not been studied; retardation of PTD was achieved through the administration of the H 2 S donor sodium sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…HMSMCs were isolated from TNL myometrial tissues following the previously described protocol ( 29 ). In brief, myometrial tissue pieces were incubated with DMEM supplemented with 1 mg/mL collagenase type II (Invitrogen) and 1 mg/mL deoxyribonuclease I at 37°C with shaking for 30 min, repeated twice.…”
Section: Methodsmentioning
confidence: 99%
“…The nitric oxide metabolites S-nitrosoglutathione (GSNO) and peroxynitrite (ONOOÀ) mediate S-nitrosation and cytotoxicity, respectively, to promote uterine relaxation and cervical remodeling. 56 Another gasotransmitter, hydrogen sulfide, inhibits the expression of contraction associated protein genes (Connexin 43 (CX-43), PTGFR, oxytocin receptor (OTR)) to suppress spontaneous contraction of the human uterus 57 and reverses the lipopolysaccharides (LPS)induced PTL by its anti-inflammatory effects. 58 Mammalian microRNAs (miRNA/miR) play especially powerful roles in smooth muscle cells and in female reproduction, wherein they have been implicated in hormone responsiveness.…”
Section: Cervical and Myometrium Modification And Remodelingmentioning
confidence: 99%